Partial Purification and Characterisation of Alkaline Phosphatase from Hepatopancreas and Intertine of Red Tilapia, (Tilapia Mossambica) - Mariappan, Vanitha (2005)
Alkaline phosphatase (EC 3.1.3.1) is a metalloenzyme, which catalyze nonspecific hydrolysis of phosphate monoesters. Partial purification was conducted on alkaline phosphatase (ALP) extracted from hepatopancreas and intestine of red tilapia, (Tilapia mossombica) using two main steps - ammonium sulphate precipitation and ion exchange chromatography on DEAE - 52. Samples from the ion-exchange step were analysed for ALP activities and characterised by SDS-PAGE. SDS-PAGE analysis showed 2 identical bands and was found to have molecular weight of 68,000 Da (hepatopancreas ALP) and 180,500 Da (intestinal ALP) subunits. Overall, purification fold obtained from the final step are 1.8 and 21.9 for hepatopancreas and intestinal respectively, with recovery of only 0.22% from hepatopancreas and 0.01% from intestine. The specific activity of the enzyme was 1.72 X 10- 2 pmol min-1 mg-1 and 2.93 X 10-1 pmol min-1 mg-1 from hepatopancreas and intestine respectively. The ALP from hepatopancreas remained stable at temperatures up to 50°C, and ALP from intestine enzyme had an optimum temperature of 60°C. The optimum pH for both hepatopancreas and intestine ALP of Tilapia mossambica is pH 10. The positive monovalent alkali metal ions (Li+, Na+ and K+) have no effect on the ALP enzyme activity. However, the positive divalent alkali metal ions (Mg2+a nd Ca2+)a ctivate the enzyme activities. Heavy metal ions (Zn2+, CU~+C,d 2+a nd Hg2+) were found to inhibit the enzyme activity.